Modernismo, archivo y estética carcelaria: encuadres contestarios y poética discrepante desde el discurso fotográfico en México (años 1920 – años 1980) - Erica Segre (IdeAs)
This article explores the modalities of a carceral aesthetics that come to prevail as part of a pacificatory figural solution; and how a style which ostensibly evidenced an incandescent cultural vitality in the arts underwent a schematization while eliciting photographic interventions which aimed to reveal the socio-cultural substratum in thrall to a system of power that persisted implicitly in the representational strategies centred on subalternity. In this way, the interdicted gaze of photography and of experimental photo-journalism, offers an opportunity to expose the measure of impunity not only in a political sense but also in relation to the art practice based on the myth of a triumphalist and sui generis modernism. In addition, by rethinking the varied works of photographers affected by this reflexive vein haunted by the operations of the frame and of deep-seated coercive power, this reading will afford an intriguing hermeneutics of totalitarian systems of information through the study of carceral paradigms (not always explicitly referenced) calqued in the guise of frame, perspective, network and image.